Do local newspapers matter to institutional investors? - Kang, Byoung Uk; Nam, Jonathan Sangwook (Contemporary Accounting Research, 2025)
Abstract This study examines the informational role of local newspapers in institutional investments. Exploring local newspaper closures across US counties, we document that institutional investors significantly reduce their holdings in firms located near the closed newspapers. The post‐closure decrease in institutional holdings is concentrated for non‐local or non–hedge fund institutions. In contrast, institutions that are likely to possess information advantages—local institutions or hedge funds—do not decrease their holdings and may even increase them when faced with a lack of local news coverage. Further analysis reveals that local newspaper closures adversely impact institutional investors' ability to predict firms' stock returns, particularly for non‐local or non–hedge fund institutions. Collectively, we provide novel evidence suggesting that local newspapers are a key channel through which institutional investors acquire geographically scattered information.